The Role of Social Capital and Local Wisdom Towards the Development of The Blue Economy - Bambang Haryadi; Driana Leniwati; Darti Djuharni; Sonhaji Sonhaji; Merie Satya Angraini (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to examine empirical evidence that social capital and local wisdom have influences on the development of the blue economy. The research approach uses mixed methods, namely quantitative and qualitative methods. To examine the effect, researchers used regression tests. Furthermore, to strengthen the results of quantitative tests, researchers deepen them using descriptive-qualitative methods. The results show: 1) social capital has influences on the development of the blue economy. Social capital could generate economic resources; 2) Local wisdom influences the development of the blue economy. Local wisdom refers to controlling the behavior of people in coastal areas so that natural resources can be used wisely. The uniqueness of this study is that this research uses a mixed method and is based on the local values of the Madurese. The results of this research can be a foundation for local governments to further develop and optimize blue economy resources for community welfare. The limitations of the research are in its scope which is only limited to Madura Island so that the implications can only be used as a benchmark in the region.